Ethnicity, gender and physiological parameters: Their effect on in vivo flavour release and perception during chewing gum consumption. (February 2019) - Pedrotti, M.; Spaccasassi, A.; Biasioli, F.; Fogliano, V.
Abstract: In this study, the impact of physiological parameters, ethnicity and gender on flavour perception and flavour release of chewing gum was investigated. Proton Transfer Reaction Mass Spectrometry in-nose monitoring of volatile organic compounds was coupled to discontinuous time intensity sensory evaluation for mint flavour and sweetness perception. Each of the 29 subjects, 14 European and 15 Chinese panelists (13 male and 16 females, age 24 ± 1.4 years old) consumed the samples in triplicates. Physiological parameters (oral cavity volume, salivary flow, acetone and isoprene concentration and fungiform papillae density) were measured. Significant differences for in vivo flavour release between Chinese and European panelists after 90 s of consumption and after the gum was removed from the mouth were found. Significant differences were observed also in flavour and sweetness perception while no gender effect was detected. In this work, for the first time an effect of ethnicity on in-nose flavour release monitored through PTR-MS was noticed during chewing gum consumption, in agreement with the findings from sensory evaluation. Single physiological parameters do not explain the relation between flavour in nose release and perception during consumption. Graphical abstract: Unlabelled Image Highlights: Real time analysis were applied to monitor aroma perception and release of mint chewing gum. A significant effect of ethnicity on aroma perception and release was found. Single physiological parameters didn't explain the relation between flavour release and perception.